N-Terminal Acetylation by NatC Is Not a General Determinant for Substrate Subcellular Localization in Saccharomyces cerevisiae - Aksnes, Henriette (Public Library of Science, 2013)

(untitled)
N-terminal acetylation has been suggested to play a role in the subcellular targeting of proteins, in particular those acetylated by the N-terminal acetyltransferase complex NatC. Based on previous positional proteomics data revealing N-terminal acetylation status and the predicted NAT substrate classes, we selected 13 suitable NatC substrates for subcellular localization studies in Saccharomyces cerevisiae. Fluorescence microscopy analysis of GFP-tagged candidates in the presence or absence of the NatC catalytic subunit Naa30 (Mak3) revealed unaltered localization patterns for all 13 candidates, thus arguing against a general role for the N-terminal acetyl group as a localization determinant. Furthermore, all organelle-localized substrates indicated undisrupted structures, thus suggesting that absence of NatC acetylation does not have a vast effect on organelle morphology in yeast.